Geographic distribution patterns of amphibians and reptiles from the Uruguayan Savanna. Issue 1 (31st December 2022) - Alvares, Diego Janisch; Ferrari, Augusto; Borges-Martins, Marcio
Abstract : We assessed the geographic distribution of amphibians and reptiles occurring in the Uruguayan Savanna ecoregion (USE) to find shared distribution patterns, in order to identify chorotypes which could inform the conflicting regionalization of the Pampa province. We compiled nearly 83, 000 records of complete geographic distributions of the 58 species of amphibians and 86 species of reptiles with occurrence in the Uruguayan Savanna throughout South America. Endemicity analysis (NDM/VNDM) was implemented to identify shared geographic distribution patterns (chorotypes). We described general diversity patterns for the Uruguayan Savanna in terms of endemic species and the degree of species shared with other ecoregions. We have found five amphibians (anurans) and nine reptiles (six lizards, two amphisbaenians, and one snake) endemic to the USE, while most species from the Uruguayan Savanna ecoregion are shared with other ecoregions. We recovered 38 consensus areas from 68 individual areas resulting in 17 chorotypes after implementing a metaconsensus cluster analysis. Our results indicate a complex pattern of shared geographic distributions between Uruguayan Savanna and adjacent biogeographical units. The limits of the ecoregion coincided with some chorotypes, however, the traditional limits of the Pampa did not align with any chorotype. The tropical affinity of the USE was supported by both the number of species shared with Alto Paraná Atlantic forests, and the pattern of chorotype recovered. Species that occur in temperate pampa and the USE were widely distributed in other ecoregions.